Role of LGMN in tumor development and its progression and connection with the tumor microenvironment - Khan, Safir Ullah; Khan, Ibrar Muhammad; Khan, Munir Ullah; Ud Din, Muhammad Azhar; Khan, Muhammad Zahoor; Khan, Nazir Muhammad; Liu, Yong (Frontiers in Molecular Biosciences, 2023)
Legumain (LGMN) has been demonstrated to be overexpressed not just in breast, prostatic, and liver tumor cells, but also in the macrophages that compose the tumor microenvironment. This supports the idea that LGMN is a pivotal protein in regulating tumor development, invasion, and dissemination. Targeting LGMN with siRNA or chemotherapeutic medicines and peptides can suppress cancer cell proliferation in culture and reduce tumor growth in vivo. Furthermore, legumain can be used as a marker for cancer detection and targeting due to its expression being significantly lower in normal cells compared to tumors or tumor-associated macrophages (TAMs). Tumor formation is influenced by aberrant expression of proteins and alterations in cellular ar-chitecture, but the tumor microenvironment is a crucial deciding factor. Legumain (LGM) is an in vivo-active cysteine protease that catalyzes the degradation of numerous proteins. Its precise bi-ological mechanism encompasses several routes, including effects on tumor-associated macro-phage and neovascular endothelium in the tumor microenvironment. The purpose of this work is to establish a rationale for thoroughly investigating the function of LGMN in the tumor micro-environment and discovering novel tumor early diagnosis markers and therapeutic targets by reviewing the role of LGMN in tumor development and progression and its connection with the tumor microenvironment.